Molecular characterization of Cyprinid herpesvirus 3 encoded viral interleukin10. Issue 89 (June 2019) - Ouyang, Ping; Yang, Ruixue; Yin, Lizi; Geng, Yi; Lai, Weiming; Huang, Xiaoli; Chen, Defang; Fang, Jing; Chen, Zhengli; Tang, Li; He, Min; Huang, Chao; et al.
Abstract: Cyprinid herpesvirus 3 (CyHV-3), a virus that encodes an interleukin10 (IL-10) homologue, causes severe economic losses to the common carp and koi culture industry. The present study was devoted to this IL-10 homologue. Recombinant viral IL-10 (vIL-10) protein encoded by CyHV-3 ORF134 gene using prokaryotic expression system was obtained successfully. Bioinformatics analysis revealed that the amino acid sequence of CyHV-3 vIL-10 has low homology with other host IL-10 or viruses encoded IL-10s. However, their tertiary structure is quite similar, suggesting conservative biological functions between IL-10s and vIL-10s. The biological activity of CyHV-3 vIL-10 was detected by using CCK-8 kit and real time quantitative PCR. The results showed that CyHV-3 vIL-10 down regulate epithelioma papulosum cyprini (EPC) cellular activity at 72 h. Moreover, CyHV-3 vIL-10 inhibits the LPS-induced expression of proinflammatory genes, similar to common carp IL-10. Altogether, the results of this study demonstrate that a clear biological activity of CyHV-3 vIL-10 on its host cells and indicates CyHV-3 vIL-10 may play an important role in viral immune evasion. Highlights: Bioinformatics analysis demonstrated that CyHV-3 vIL-10 function is conserved compared to IL-10s or other vIL-10s. CyHV-3 vIL-10 down regulates EPC cells cellular activity at 72 h. CyHV-3 vIL-10 inhibits the LPS-induced expression of proinflammatory genes, similar to common carp IL-10. CyHV-3 vIL-10 may play a role in viral immune evasion.